Cerebral vein thrombosis in Behçet's disease - (:unkn) unknown (My University, 2001)
Behçet's disease is a chronic, relapsing multisystem disorder, and nervous system involvement is one of the serious manifestations. Neuro-Behçet is rarely reported in children and may present with a wide variety of symptoms because the entire neuraxis may be affected. A case of cerebral vein thrombosis secondary to Behçet's disease is presented. The patient has recovered without any visual loss and had no complaints at 1-year follow-up.
Keywords: Female; Humans; Behcet Syndrome; Adolescent; Magnetic Resonance Imaging; Diagnosis, Differential; Headache; Nausea; Vomiting; Phlebography; Oral Ulcer; Cerebral Veins; Intracranial Hypertension; Lateral Sinus Thrombosis